VISUAL SYMPTOMS OF PPV INFECTION ON LEAVES IN A PLUM COLLECTION IN RELATION TO THE SUSCEPTIBILITY OF VARIETIES AND PLANTING AGE [VIZUÁLNÍ PŘÍZNAKY INFEKCE PPV NA LISTECH V KOLEKCI SLIVONÍ VZHLEDEM K CITLIVOSTI GENOTYPŮ A STÁŘÍ VÝSADBY] - Boris Krška; Michaela Marklová; Liliia Pavliuk; Pavel Pech (Vědecké Práce Ovocnářské)
The occurrence of Potyvirus plumpoxi has a major impact on the economic importance of plum trees. Potyvirus plumpoxi is a dangerous pathogen that causes disease in all stone fruits worldwide. It is therefore important to understand the characteristics and spread of this virus. The course of the disease and the expression of symptoms depend on several factors such as the air temperature, the age of tree and the variety. Therefore, our objective was to observe the manifestation of symptoms of Potyvirus plumpoxi infection in plum trees of different varieties from 2015 to 2023. During the study, the intensity of symptoms was studied in relation to the variety and planting age. The varieties studied were divided into several categories based on the intensity and stability of symptom expression.